Development of a position tracking drive system for controlling PMSM motor using dSPACE 1104-based variable structure - Tran Duc Chuyen; Nguyen Duc Dien (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
In industrial electric drive systems, it is common to find objects that need to solve the problem of angular position control, moving the object from one position to another asymptotically with no over-correction and guarantee. calculation of maximum fast impact. This is a multi-target optimization problem with many different solutions. This paper presents a method of constructing a PMSM motor position controller with a variable structure using dSPACE 1104 card. The system consists of a position control loop with a variable structure that is an outer loop and a speed control loop degree is the inner loop. In which, the speed adjustment loop uses adaptive law to compensate for uncertain functions and build a sliding mode observation to estimate load torque, friction and noise. The results of the simulation study were verified on Matlab-Simulink environment and experimented on dSPACE 1104 card to check the correctness of the built controller algorithm. The research results in the paper are the basis for the evaluation and setting up of control algorithms, design of electric drive systems in industry and the military.